REPRESENTATIVE REGISTRATIONS OF EARTHQUAKES WITH DEVELOPMENT OF THE NET OF SEISMIC OBSERVATIONS IN THE CAUCASUS: (catalogue of main earthquakes) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
In this work the history of development of instrumental observations done in the Caucasus before and after the devastating earthquake of Spitak of 1988 is given. The representative registrations are calculated that is very important for the study of seismic activity of the territory. In this article is indicated, where can be taken the data of the catalogue of the main parameters of the earthquakes of the Caucasus. The development of the observation net will enable to graduate the whole period and receive identical data for the region and particularly for the territory of RA.
Keywords: unifiled seismic database; station; epicenter